Charge density wave soliton liquid. (2nd February 2015) - Matsuura, T.; Hara, J.; Inagaki, K.; Tsubota, M.; Hosokawa, T.; Tanda, S.
Abstract: We investigate the charge density wave transport in a quasi–one-dimensional conductor, orthorhombic tantalum trisulfide ( o -TaS3 ), by applying a radio-frequency ac voltage. We find a new ac-dc interference spectrum in the differential conductance, which appears on both sides of the zero-bias peak. The frequency and amplitude dependences of the new spectrum do not correspond to those of any usual ac-dc interference spectrum (Shapiro steps). The results suggest that CDW phase dynamics has a hidden degree of freedom. We propose a model in which phase solitons behave as liquid. The origin of the new spectrum is that the solitons are depinned from impurity potentials assisted by an ac field when a small dc field is applied. Our results provide a new insight as regards our understanding of an elementary process in CDW dynamics.